Is there a (viable) crucial-case method? - Gerring, John (2007)
Case study researchers use diverse methods to select their cases, a matter that has elicited considerable comment and no little consternation. Of all these methods, perhaps the most controversial is the crucial-case method, first proposed by Harry Eckstein several decades ago. Since Eckstein's influential essay, the crucial-case approach has been used in a multitude of studies across several social science disciplines and has come to be recognized as a staple of the case study method. Yet the idea of any single case playing a crucial (or critical) role is not widely accepted. In this article, the method of the crucial case is explored, and a limited defense (somewhat less expansive than that envisioned by Eckstein) of that method is undertaken. A second method of case-selection, closely associated with the logic of the crucial case, is introduced: the pathway case. - Reproduced.
Keywords: Case Studies